Effects of High-Intensity Interval vs. Continuous Moderate Exercise on Intraocular Pressure - Conte, M.; Baldin, A. D.; Russo, M. R. R. R.; Storti, L. R.; Caldara, A. A.; Cozza, H. F. P.; Ciolac, Emmanuel Gomes [UNESP] (Georg Thieme Verlag Kg, 2014)
Our purpose was to compare the acute effects of high-intensity interval training (HIT) vs. continuous moderate exercise (CME) on intraocular pressure (IOP) in healthy subjects. Fifteen young men (age = 22.1 +/- 6 years) underwent 30 min of HIT (2 min of walking at 50 % of reserve heart rate (HR) alternated with 1 min of running at 80 % of reserve HR) and CME sessions (30 min of jogging/running at 60 % of reserve HR) in random order (2-5 days between sessions). IOP was measured before (baseline), immediately after (post-exercise), 5 min after (Rec5) and 10 min after (Rec10) each exercise session. IOP was reduced post-exercise and remained reduced at Rec5 during both HIT and CME session, with no significant difference between interventions (similar to 16 % between 23 %). However, IOP remained reduced at Rec10 only after HIT intervention (similar to 19 %), whereas IOP at Rec10 returned to levels similar to the observed at baseline during CME intervention. In summary, both HIT and CME equally reduced IOP immediately and 5 min after exercise session. However, only HIT was able to remain IOP reduced 10 min after exercise. These results suggest that HIT may be more effective than CME for reducing IOP in young healthy men.
Keywords: aerobic exercise; glaucoma; high-intensity interval training; intraocular pressure